Searching of flat waves of density in spatial distribution of quasars - Khodyachikh, M. (Кинематика и физика небесных тел, 2005)
Periodicity in galaxy distribution on distances was detected in pencil beams of deep redshifts surveys of galaxies. A priori probability of the appearance of such periodicity is 10−8 [5] even at the presence of the selected scale in a correlation function. Eynasto et al. [4] exposed a moderately regular net structure in the distribution of rich clusters of galaxies and voids. They consider that it must be due to a process unknown before. It can be assume that in some directions there are flat waves of density. The discovery of periodicities in pencil surveys is possible not far from these directions. Superposition of waves of different directions and with different periods can lead to the appearance of regular net structure. The search of flat waves of density in the spatial distribution of quasars with the periods in the range (230–700)h⁻¹ Mpc, most favourable for their exposure, has been carried out. The samples of quasars from catalogues of Veron-Cetti, Veron and 2QZ 10k were used. While scanning the sky the power spectra of quasars distribution along an axis of sight were analysed. Four flat waves, presented in various not intersected samples with periods coincided within the limits of spectral resolution and with close phases were detected. Estimations of parameter of density have been made in each of them. Mean value is 0.29±0.02 (95% confidence limit).